Resolving Bad Credit for Blacklisted MSMEs at PT Bank Rakyat Indonesia Gondosari Kudus Unit - Wulandari, Miladianur; Mahmudah, Siti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Many credit capital is used as a way to develop a business or start a business. However, there are quite a few that can save credit from various problems. So there needs to be a solutionconcrete way to overcome the problem of blacklisted bad credit. The main problem of this research is about the policy of the Bank Rakyat Indonesia Gondosari Kudus Unit in resolving bad credit for blacklisted MSMEs and how to implement the policy for resolving bad credit for blacklisted MSMEs. This research uses empirical juridical methods. This study aims to determinepImplementation of policies for resolving bad credit for MSMEs that are blacklisted and how the policy of the Indonesian People's Bank, Gondosari Kudus Unit regarding resolving bad loans of blacklisted MSME debtors.Resolving blacklisted bad credit can be done by submitting a credit agreement restructuring application. Furthermore, settlement can also be done through the Bank Indonesia Dispute Resolution Agency. The last is settlement through court. Settlement through court is the stage of resolving bad credit which is carried out through legal channels.